2013
DOI: 10.1002/jcp.24422
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-22, miR-24 and miR-34a as novel predictive biomarkers to pemetrexed-based chemotherapy in advanced non small cell lung cancer

Abstract: Pemetrexed has been widely used in patients with advanced non-small cell lung cancer (NSCLC). The clinical relevance of polymorphisms of folate pathway genes for pemetrexed metabolism have not been fully elucidated yet. The aim of this study was to evaluate the expression levels of circulating miR-22, miR-24, and miR-34a, possibly involved in folate pathway, in NSCLC patients treated with pemetrexed compared with healthy controls and to investigate their impact on patient clinical outcomes. A total of 22 conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 17 publications
4
63
1
1
Order By: Relevance
“…Expression of the miR-34 family was downregulated in tumor tissue compared with normal tissue, and low levels of miR-34a expression were associated with a higher probability of relapse in surgically resected NSCLC (28). However, higher levels of circulating miR-34a were observed in patients with NSCLC compared with healthy controls (29). Higher levels of miR-34a indicated a shorter OS time in patients receiving palliative platinum derivate-based chemotherapy in combination with gemcitabine in the present study.…”
Section: Discussioncontrasting
confidence: 38%
“…Expression of the miR-34 family was downregulated in tumor tissue compared with normal tissue, and low levels of miR-34a expression were associated with a higher probability of relapse in surgically resected NSCLC (28). However, higher levels of circulating miR-34a were observed in patients with NSCLC compared with healthy controls (29). Higher levels of miR-34a indicated a shorter OS time in patients receiving palliative platinum derivate-based chemotherapy in combination with gemcitabine in the present study.…”
Section: Discussioncontrasting
confidence: 38%
“…Likely to cellular miRNAs, studies suggested that changes in the profile of circulating miRNAs are correlated with a pathophysiological condition of human cancer. In line with this concept, data achieved from our studies indicated that blood levels of miR-22, miR-24 and miR-34a are correlated with advanced stages of non-small cell lung cancer (NSCLC) (25). Also, several other cell-free miRNAs (e.g.…”
Section: Circulating Mirnas In Cancer Diagnosissupporting
confidence: 71%
“…It inhibits cell cycle progression by repressing Max and ErbB3 expression post-transcriptionally, mediates the effects of the tumor-suppressor p53, and suppresses interferon gene expression by blocking interferon regulatory factor-5 [49][50][51] . MiR-22 has been proposed as a potential serum marker for non-small cell lung cancer [52] , esophageal squamous cell carcinoma [53] , and nasopharyngeal carcinoma [54] . Our experimental strategy in this study focused on using hybridization-based microarray technology as the means to screen thousands of genes simultaneously, but it is also severely limited due to its issues with reproducibility and its tendency to produce a high rate of false positive and false negative results.…”
Section: Discussionmentioning
confidence: 99%